2015
DOI: 10.1002/bip.22605
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and mechanism of action of a novel cationic α‐helical octadecapeptide derived from α‐amylase of rice

Abstract: AmyI-1-18, an octadecapeptide derived from α-amylase (AmyI-1) of rice (Oryza sativa L. japonica), is a novel cationic α-helical antimicrobial peptide (AMP) that contains two lysine and two arginine residues. The antimicrobial activity of AmyI-1-18 against human pathogens was quantitatively evaluated using a chemiluminescence method that measures ATP derived from viable cells. Of the ten kinds of human pathogens, AmyI-1-18 exhibited antimicrobial activity against nine. Its 50% growth-inhibitory concentrations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 58 publications
(116 reference statements)
6
54
0
Order By: Relevance
“…4). The almost negligible differences in both the EC 50 and K D of AmyI-1-18 between LPS and lipid A strongly supported the assertion that AmyI-1-18 specifically binds to the lipid A moiety of LPS through electrostatic and hydrophobic interactions and thereby is capable of detoxifying these endotoxins. In our previous study [45], we reported the ability of CL (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) to inhibit NO production in RAW264 cells stimulated with LPS or lipid A from E. coli CL(14-25) significantly repressed endotoxin-induced NO production in mouse microphage cells.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…4). The almost negligible differences in both the EC 50 and K D of AmyI-1-18 between LPS and lipid A strongly supported the assertion that AmyI-1-18 specifically binds to the lipid A moiety of LPS through electrostatic and hydrophobic interactions and thereby is capable of detoxifying these endotoxins. In our previous study [45], we reported the ability of CL (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) to inhibit NO production in RAW264 cells stimulated with LPS or lipid A from E. coli CL(14-25) significantly repressed endotoxin-induced NO production in mouse microphage cells.…”
Section: Discussionmentioning
confidence: 54%
“…In our previous studies, we reported that AmyI-1-18 is a cationic and amphipathic AMP derived from ␣-amylase (AmyI-1) of rice and that this peptide exhibited antimicrobial activity against several human pathogens [50]. In this study, as another host defense function of AmyI-1-18, we investigated its ability to inhibit NO induction in RAW264 cells stimulated with endotoxins (LPSs or lipid A from E. coli) because NO is believed to have an important role in the pathogenesis of inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations